Scaring the Already Scared: Some Problems With HIV/AIDS Fear Appeals in Namibia. - Muthusamy, Nithya; Levine, Timothy R.; Weber, Rene (Journal of Communication, 2009)
Fear appeals are often used in public health campaigns in Africa to prevent further spread of HIV/AIDS. Based on the extended parallel processing model framework (K. Witte, 1991), this research assessed the impact of such messages in a high-fear situation. A 2 (high threat, low threat) × 2 (high efficacy, no efficacy) experiment with a no-message offset control and efficacy-only conditions tested several predictions. Participants demonstrated high preexisting fear about HIV/AIDS. As a likely consequence, statistical equivalence tests indicated that messages' threat levels had little impact on perceptions of fear or on outcome measures such as attitudes, intentions, or behaviors. It is concluded that the use of fear appeals to persuade audience with high levels of preexisting fear is ill-advised and ineffective.